Comparative studies between guidelines and actual practice of safety on site in perspective of PPE - Ayu Andirah, Sakka (2016)
Accident in construction industry still occurs even with the enforcement of safety. Workers fail to follow the proper procedures for minimizing hazard and the safety guideline in site .Personal Protective Equipment (PPE) can be significant determining factors between hazard and safety on construction site. The practice of safety guidelines in perspective of PPE with the smallest differential in adoption of actual practice contribute on the occurrence of accidents and its frequencies in Malaysia. This research aims to find out the comparative studies between actual safety on site and DOSH guidelines, determine factors why workers not follow safety guidelines and discuss method to minimize Safety issues on site so advance precaution can be taken to lessen the numbers of accidents. The scope of this research is based on a current construction project in Setapak, Kuala Lumpur area. Site based data collection entailed interview of safety officer or parties that responsible for the safety on site and DOSH officer regarding to the safety.